2009
DOI: 10.5194/acp-9-5587-2009
|View full text |Cite
|
Sign up to set email alerts
|

Tropical cyclogenesis in a tropical wave critical layer: easterly waves

Abstract: Abstract. The development of tropical depressions within tropical waves over the Atlantic and eastern Pacific is usually preceded by a "surface low along the wave" as if to suggest a hybrid wave-vortex structure in which flow streamlines not only undulate with the waves, but form a closed circulation in the lower troposphere surrounding the low. This structure, equatorward of the easterly jet axis, is identified herein as the familiar critical layer of waves in shear flow, a flow configuration which arguably p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
282
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(303 citation statements)
references
References 169 publications
20
282
1
Order By: Relevance
“…More precisely, genesis occurs near the intersection of the disturbance's 700-hPa trough axis and the zero-relative-flow isopleth. This behavior is consistent with the ''marsupial'' paradigm of TC genesis from easterly waves, recently proposed by Dunkerton et al (2009). As its name suggests, the marsupial paradigm envisions the closed gyre circulation of an easterly wave critical layer as being especially favorable for TC genesis, by protecting the incipient storm from the detrimental effects of horizontal mixing and straining, analogous to a joey inside a mother kangaroo's pouch.…”
Section: Easterly Waves and Tc Genesissupporting
confidence: 68%
“…More precisely, genesis occurs near the intersection of the disturbance's 700-hPa trough axis and the zero-relative-flow isopleth. This behavior is consistent with the ''marsupial'' paradigm of TC genesis from easterly waves, recently proposed by Dunkerton et al (2009). As its name suggests, the marsupial paradigm envisions the closed gyre circulation of an easterly wave critical layer as being especially favorable for TC genesis, by protecting the incipient storm from the detrimental effects of horizontal mixing and straining, analogous to a joey inside a mother kangaroo's pouch.…”
Section: Easterly Waves and Tc Genesissupporting
confidence: 68%
“…Using the RGB and averaging all cases contributing to the number of occurrences in it, we construct a composite of strong off-shore BVs. This approach is complementary in philosophy to a moving framework of reference as suggested by Dunkerton et al (2009). Instead of tracking one vortex in a flow-following coordinate system, we select all vortices with similar properties that have occurred over a certain period of time at a given location.…”
Section: Methodsmentioning
confidence: 99%
“…Raymond and López Carrillo (2011) found that vertically overlapping closed circulations in the boundary layer and at 5-km elevation provided a deep region of protection from negative environmental influences during the formation of TY Nuri. Montgomery et al (2010) suggested that despite the detrimental influences of strong vertical wind shear and dry air during the early stages of TY Nuri, the presence of a quasi-closed circulation in the system-relative frame (wave pouch) characterized by recirculating flow (Dunkerton et al 2009) protected the incipient vortex until it could reach a more favorable environment. They further hypothesized that an increase in the depth of the wave pouch is favorable for storm formation and may have occurred prior to the formation of TY Nuri.…”
Section: Introductionmentioning
confidence: 99%